Pembaharuan Pendidikan Islam di Indonesia - Saidur Ridlo (STAI Syaichona Moh. Cholil Bangkalan, 2020)
Abstract: The long journey of Islamic education has colored the tumult of models of Islamic education in various regions, especially in Indonesia itself, Islamic education also took the momentum of turmoil and renewal in various parts of other Islamic regions. That Effect had a significant impact to call it a change, both in the ideological and practical domains. Of course That turmoil has colored the reform process and determine the goal of renewal of Islamic education in Indonesia, on the other hand, the result of it sometimes made a resistence which illustrates how dynamic the journey of Islamic education in Indonesia, It can be seen from the diversity of Islamic education models that have taken root for years, moreover, the seeds of Islamic educational institutions have flourished several centuries ago.